UZBEKISTAN MAQOM ART: HISTORICAL DEVELOPMENT AND REGIONAL TRADITIONS - Xaydarova Rozaxon (Modern American Journals, 2025)
This article explores the historical development and regional traditions of Uzbek maqam music. It analyzes key schools such as the Bukhara Shashmaqom, Khorezm maqams, and the maqam repertoires of Fergana and Tashkent, highlighting their aesthetic and cultural significance. Special attention is given to the scholarly contributions of Dr. Ishoq Rajabov, the sacred status of maqams, and the continuity of oral traditions. The maqam is presented as an invaluable cultural heritage that reflects the spiritual and national identity of the Uzbek people.
Keywords: Maqam, Shashmaqom, Duvozdahmaqom, Khorezm maqams, Fergana maqams, Ishoq Rajabov, musical heritage, oral tradition, national music culture.